ANALISIS PERKEMBANGBIAKAN TUMBUHAN SECARA VEGETATIF BUATAN (MENCANGKOK ) POHON JERUK LEMON (CITRUS LEMON) - Sundari Sundari; Seila Mariska (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Citrus limon, also known locally as lemon, is a member of the Rutaceae family and is often grown in South Asian countries. Lemons are widely recognized as a horticultural commodity and offer a wider variety of uses than other citrus fruits. Lemons offer significant potential and represent a promising market opportunity for intensive cultivation. Availability of high-quality seedlings in sufficient quantities, within a relatively short timeframe, and at affordable prices are crucial initial steps to ensure success in this lemon cultivation endeavor. One method of vegetative propagation that can be applied to lemon plants is grafting.